Cognitive function among older adults: ELSI-Brazil results - Erico Castro-Costa; Maria Fernanda Lima-Costa; Fabíola Bof de Andrade; Paulo Roberto Borges de Souza Junior; Cleusa Pinheiro Ferri (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To investigate macroregional variations in cognitive function in a national sample representative of the Brazilian population aged 50 years and older. METHODS Data from the baseline of the Longitudinal Study of Brazilian Elderly (ELSI-Brazil), collected between 2015 and 2016, were used. Memory was measured by means of a 10-word list and executive function, by semantic verbal fluency, based on the naming of animals. Gender, age, education, and rural or urban residence were potentially confounding RESULTS Among the 9,412 ELSI-Brazil participants, 9,085 were included in the analysis; 53.9% were women and the average age was 63.0 (0.42) years. After adjusting for potential confounding variables, average scores for memory and verbal fluency were lower in the Northeast region and higher in the Midwest and Southeast, respectively. In the South region, higher scores were found for immediate and combined memory. In all regions, older participants and those with lower schooling had worse scores for memory and verbal fluency. CONCLUSIONS There are differences in cognitive function among older adults in the different macroregions, independent of age, gender, schooling, and rural or urban residence.